Pendampingan Perencanaan Cash Flow dan Cash Control CV. Ada Nada - Ainiyah, Nur; Nugroho, Tatas Ridho; Setiono, Hari; Ilmiddaviq, M. Bahril (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
ABSTRACT To prevent losses and be able to reach maximum profits, construction service organizations have a distinct need to plan costs through effective cash flow planning and control. This support helps spread awareness of the significance of cash flow planning and management in the construction service industry. consequently CV. Ada Nada is a company that offers construction services. She believes that good money management is essential. Due to limitations from several factors, the mentoring program's results this time are still far from ideal. The achievement of results is significantly impacted by factors related to education and human resources in addition to the quick program implementation period. Human resources may slow down production since, while having strata 1 and strata 2 education, they lack an accounting background and must learn it from scratch.